Improvement of Oxidative Stability and Microbial Shelf Life of Vanilla Cake by Coconut Oil Meal and Sesame Oil Meal Phenolic Extracts. (22nd November 2019) - Senanayake, Chathuri M.; Algama, C. Harshani; Wimalasekara, Ruwani L.; Weerakoon, W. N. M. T. D. N.; Jayathilaka, Nimanthi; Seneviratne, Kapila N.
Abstract : Phenolic extracts of coconut oil meal (CME) and sesame oil meal (SME) were compared with synthetic antioxidants for the potential of improving shelf life of vanilla cake. CME maintained hexanal (product of chemical spoilage) levels below 0.3 mg/kg in cake up to 14 days. BHT- and SME-added cakes maintained hexanal levels below 2 mg/kg, while control cake with no added antioxidants exceeded this level by day 14. Both CME and SME extended the microbial shelf life up to 13 days, while control and BHT-added cake exceeded the maximum allowed colony count by day 7 and day 11, respectively. The results indicate that the onset of microbial spoilage of vanilla cake is faster than the chemical spoilage, and addition of CME and SME extends both microbiological and chemical stability of cakes beyond day 7 during storage. Over 90% of the antioxidant activity of CME and SME retained after heating at 180°C for 2 h. CME and SME are ideal thermally stable natural alternatives for synthetic antioxidants in vanilla cake.